515 Metabolic reprogramming of antitumor CD8+ T cell immunity. (10th December 2020) - Jaccard, Alison; Wenes, Mathias; Gyülvészi, Gábor; Ho, Ping-Chih; Romero, Pedro
Abstract : Background: Adoptive cell transfer (ACT) therapies are successfully used in the clinic; however, a large fraction of patients remains unresponsive. The limited efficacy of this therapy is due, in part, to the terminally differentiated state of transferred T cells, which limits their proliferation and long-lasting antitumor response. Memory CD8+ T cells display specific phenotypic and functional characteristics endowing them with the ability to provide a more robust and long-lasting antitumor immune response than their terminally differentiated counterparts. The development and fitness of memory T cells was recently shown to be associated with specific metabolic pathways. Methods: We aimed to metabolically reprogram CD8+ T cells in order to generate fitter memory-like T cells prior to ACT. Results: We have found that pharmacological inhibition of the metabolic enzyme isocitrate dehydrogenase 2 (IDH2) during the priming of CD8+ T cells led to an increased memory formation and to an enhanced tumor growth inhibition upon ACT into melanoma tumor-bearing mice. Interestingly, IDH2 inhibition was associated with increased histone methylation and acetylation. We show that these histone modifications were required to induce the observed memory phenotype. Conclusions: These results suggest a novel strategy to promote stable memory T cell differentiation by epigenetic processes induced by metabolic reprogramming during T cell priming. These findings might be exploited to optimize ACT immunotherapy against cancer.